Mapping and Characterization of the fefe Gene That Controls Iron Uptake in Melon (Cucumis melo L.) - Ramamurthy, Raghuprakash Kastoori; Waters, Brian M. (Frontiers in Plant Science, 2017)
Iron (Fe) deficiency in plants limits crop growth and productivity. Molecular mechanisms that plants use to sense and respond to Fe deficiency by coordinated expression of Fe-uptake genes are not fully understood. The C940-fe chlorotic melon (Cucumis melo) mutant known as fefe is unable to upregulate Fe-uptake genes, however the FeFe gene had not been identified. In this study, we used two F2 mapping populations to map and identify the fefe gene as bHLH38, a homolog of subgroup Ib bHLH genes from Arabidopsis thaliana that are involved in transcriptional regulation of Fe-uptake genes in partnership with the FIT gene. A Ty1-copia type retrotransposon insertion of 5.056 kb within bHLH38 is responsible for the defect in bHLH38 in fefe, based on sequencing and expression analysis. This retrotransposon insertion results in multiple non-functional transcripts expected to result in an altered and truncated protein sequence. Hairy root transformation of fefe plants using wild-type bHLH38 resulted in functional complementation of the chlorotic fefe phenotype. Using a yeast-2-hybrid assay, the transcription factor Fit interacted with the wild-type bHLH38 protein, but did not interact with the fefe bHLH38 protein, suggesting that heterodimer formation of Fit/bHLH38 to regulate Fe-uptake genes does not occur in fefe roots. The second subgroup Ib bHLH gene in the melon genome is not functionally redundant to bHLH38, in contrast to Arabidopsis where four subgroup Ib bHLH genes are functionally redundant. Whereas the Arabidopsis bHLH transcript levels are upregulated by Fe deficiency, melon bHLH38 was not regulated at the transcript level. Thus, the fefe mutant may provide a platform for studying bHLH38 genes and proteins from other plant species.